A safety analysis of edaravone (MCI-186) during the first six cycles (24 weeks) of amyotrophic lateral sclerosis (ALS) therapy from the double-blind period in three randomized, placebo-controlled studies. (31st October 2017) - Kalin, Alexander; Medina-Paraiso, Elvia; Ishizaki, Kaoru; Kim, Alex; Zhang, Yannong; Saita, Takanori; Wasaki, Masahiko
Abstract: Background : There continues to be a need for new therapies to treat ALS. Objective : Provide an overview of safety for edaravone in ALS patients during the first six cycles of treatment. Methods : Analysis was based on three randomised, placebo-controlled clinical trials. Endpoints included treatment-emergent adverse events (TEAEs), including AEs leading to discontinuation, serious adverse events (SAEs), and deaths. Results : The analysis included a total of 368 patients (184 in the edaravone group and placebo group, respectively). Of those, 94.6% of the edaravone group and 90.2% of placebo group completed six cycles of therapy. Baseline characteristics were comparable between the two groups. TEAE incidence in the edaravone group and placebo group was 87.5% and 87.0%, respectively. TEAEs ocurring at ≥2% incidence in the edaravone group compared to placebo were contusion (14.7% vs. 8.7%), gait disturbance (12.5% vs. 9.2%), headache (8.2% vs. 5.4%), eczema (6.5% vs. 2.2%), dermatitis contact (6.0% vs. 3.3%), respiratory disorder (4.3% vs. 1.1%), and glucose urine present (3.8% vs. 1.6%). There was no imbalance in TEAEs leading to discontinuation (2.2% [edaravone], and 5.4% [placebo]). SAE incidence was 17.4% in the edaravone group and 22.3% in placebo group. Treatment-emergent deaths occurred in 2.2% in the edaravone group and 1.1% in placebo group, all respiratory in nature and attributed to worsening ALS. Conclusion : Data collected from three double-blind assessments found that while some TEAEs were more common in the edaravone group compared to placebo, the overall incidences of SAEs, deaths, and discontinuations due to AEs were similar or less for edaravone compared to placebo.